Higher Education Journals: An Emerging Field - Tight, Malcolm (International Higher Education, 2018)
This article focuses on peer-reviewed academic journals published in English that focus exclusively on higher education. It seeks to address a number of questions: How many are they? What do they focus on? Who owns them? Where are they based? How old are they? How much do they publish? Which are the best? What does the future hold?